Initial Experiences of Laparoscopic Surgery at Nobel Medical College Teaching Hospital: A Learning Curve - Subedi, Shanti; GC, Narayan; Lamichhane, Sabina; Chhetri, Manisha (Journal of Lumbini Medical College, 2017)
Introduction: The field of minimal invasive surgery has flowered explosively in the recent past. Modern endoscopy has changed the approach to diagnosis as well as the operative procedure. This study was done with the aim of sharing the experiences of gynecological laparoscopic procedures done at Nobel Medical College and Teaching Hospital, Nepal. Methods: A descriptive study was done in the department of Obstetrics and Gynecology, Nobel Medical College from 1stFebruary 2015 to 30thJanuary 2016. All the patients undergoing laparoscopic procedures were analyzed for the indication, type of procedures and their complications. Results: During the study period, 100 patients underwent laparoscopic procedures including 25 cases of diagnostic and 75 cases of therapeutic procedures. Fifty-three patients with an ovarian mass underwent laparoscopic cystectomy. Laparoscopic salpingectomy was done in 11 patients with ectopic pregnancy. Laparoscopy assisted vaginal hysterectomy (LAVH) was done in eight cases and laparoscopic sterilization in two cases. One patient underwent successful myomectomy. One patient undergoing laparoscopic cystectomy and one case of LAVH had conversion to laparotomy because of dense adhesion and vault bleeding respectively. No other major complication noted apart from port side bleeding, infection and vault hematoma. Conclusion: Laparoscopy is a safe and feasible alternative to open gynecological surgeries though it has a long learning curve and a lot of expertise is necessary. DOI: https://doi.org/10.22502/jlmc.v4i1.77 J. Lumbini. Med. Coll.Vol 4, No 1, Jan-June 2016, page: 20-23